POSSIBILITIES OF DEVELOPMENT OF THE SLOW TOURISM CONCEPT IN ROMANIA - Alina MARCUTA; Liviu MARCUTA; Agatha POPESCU; Cristina TINDECHE; Valentina TUDOR; Dragos SMEDESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Slow tourism, slow adventure are new ways to travel, are new ways of life that are addressed to a new generation of tourists, much more concerned with ecology, environmental protection, and who wants to have a relaxing break after life tumultuous it has, which needs both adrenaline, but also immersion in a natural, open space, which will allow them to disconnect from technology. Drawing from these concepts, appeared and developed by specialists from the Nordic countries, as well as from the examples of their good practices, through this paper we set out to analyze the evolution of tourism worldwide during the period 2009-2018, with the purpose of to identify the ways of adapting Romania to these new temptations. The research method consisted of two stages, one of bibliographic study and another of analysis and interpretation of statistical data, on the basis of which conclusions could be formulated and proposals made for the development of slow tourism.